KUALITAS PRODUK DAN CELEBRITY ENDORSER DALAM MENENTUKAN MINAT BELI PRODUK MS GLOW MELALUI BRAND IMAGE SEBAGAI VARIABEL INTERVENING DI HANAA BEAUTY STORE SITUBONDO - Jannah, Fenina Wierdatul; Karnadi, Karnadi; Harisandi, Yudhistira (Fakultas Ekonomi dan Bisnis, 2022)
The life sustainability of the company in a very competitive competition requires good management in order to be able to maximize product sales, especially at the Hanaa Beauty Store Situbondo. The purpose of this study was to examine the effect of product quality and celebrity endorser on custmer buying interest through brand image as an intervening variable at Hanaa Beauty Store Situbondo. This research is an explanatory research. The population in this study were consumers of Ms Glow product at Hanaa Beauty Store Situbondo. The sampling technique in this study was determined by simple random sampling. The data analisys and hypothesis testing in this study used a structural equation model – partial least square (PLS-SEM). The results of the direct influence hypothesis test using PLS 3.0, show that product quality has a positive but not significant effect on brand image, celebrity endorser has a significant positive effect on brand image, product quality has a significant positive effect on buying interest consumers, celebrity endorser has a significant positive effect on consumer buying interest. The results of the indicate that the product quality variable on consumer buying interest through brand image has a positive but not significant effect, celebrity endorser on consumer buying interest through brand image has a significant positive effect.